Aspects of social life of the city Algiers in the writings of the French consuls during the eighteenth century “laugier de tassy and Cesaire Phillippe Valliere” as a models - djilali zourgui, Warda; khaldi, belarbi (The Algerian Historical Journal, 2026)
Algeria knew in during a period Ottoman the influx of many foreigners, such as consuls, travelers and captive... Most of them left us notes talking about Algeria while they were there, they described the city's society (especially) in various political, social, cultural and other fields. his study purpose, to shed light on some aspects of social life in the city of Algeria during the 18th century, through two models of the writings of the French consuls, namely lauger de tassy and Cesaire Phillippe Valliere. Through this research paper, we tried to introduce these writings and their authors, in addition the images and impressions left by the two consuls about the city of Algiers